The Influence of Leadership Style on the Performance Productivity of Members in Campus Organizations (Study at the University of Riau Student Executive Institution) - Muhammad Abdul Yazid; Achmad Hidir (CV. Rayyan Dwi Bharata, 2024)
Human resource management is defined as a process for recruiting, developing, motivating and evaluating all required human resources. The research method used is a quantitative method with an explanatory approach and questionnaires for data collection. The population in this study were members of the Student Executive Board of Riau University. In determining the sample, the Slovin formula was used with a total of 62 respondents using proportionate random sampling technique. This research was processed and analyzed using SPSS 2. The research results show that the results of the F test show that based on the output data, it is known that the F value = 15.898 with a significance level of 0.000. Thus, the significance level obtained at 0.000 is smaller than α = 0.05 and the Fcount obtained at 15.898 is greater than Ftable, namely 3.03. It can be concluded that there is an influence of leadership style on the productivity of members' performance in campus organizations (Studies in Executive Boards Riau University student). Thus Ho is rejected and Ha is accepted.